Optimisation of feedwater heaters and geothermal preheater in fossil-geothermal hybrid power plant - Nsanzubuhoro, Christa (Department of Mechanical Engineering, 2020)
Sufficient energy supply is a fundamental necessity for the stimulation of socio-economic advancement. However, the current rapid rise in urbanisation has resulted in the significant increase in energy demands. Consequently, the current conventional energy supply systems are facing numerous challenges in meeting the world's growing demand for energy sustainably. Thus, there is an urgent and compelling need to develop innovative, more effective ways to integrate sustainable renewable energy solutions into the already existing systems or better yet, create new systems that all together make use of renewable energy. This research aims to investigate and establish the optimum working conditions of a feedwater heater and geothermal preheater in a power plant that makes use of both renewable and non-renewable energy resources, where renewable energy (geothermal energy) is used to boost the power output in an environmentally sustainable way. Henceforth, a simplified model of a Rankine cycle with single reheat and regeneration and another model with a geothermal preheater substituting the low-pressure feedwater heater were designed. The Engineering Equations Solver (EES) software was used to perform an analysis of the thermodynamic performance of the two models designed. The models were used to analyse the energetic and exergetic effects of replacing a low-pressure feedwater heater with a geothermal preheater sourcing heat from a low temperature geothermal resource (temperature generally < 150°C). The results of this research work reveal that the replacement of the low-pressure feedwater heater with a geothermal preheater increases the power generated since less heat is bled from the low-pressure turbine (allowing more heat energy from the steam to be converted into mechanical energy in the turbine). Applying the principle of the Second Law of thermodynamics analysis, the Number of Entropy Generation Units (EGU) and Entropy Generation Minimisation (EGM) analysis were employed to optimise the designed hybrid system. The feedwater heaters and geothermal preheater were modelled as counter-flow heat exchangers and a downhole co-axial heat exchanger, respectively. The feedwater heaters were optimised by means of the method of Number of Entropy Generation Units whereas the geothermal preheater was optimised by means of the Entropy Generation Minimisation analysis method. Owing to the optimisation of these components, the operating conditions of the boiler and turbines were secondarily improved. Overall, this research emphasises the impact renewable energy has on major power plant systems that are in operation and run on non-renewables.